PROSES BERPIKIR VISUAL SISWA TUNAGRAHITA RINGAN DALAM MEMAHAMI SEGIEMPAT BERBANTUAN MEDIA ORIGAMI - Susanto, S; Aini, Nur; Trapsilasiwi, Dinawati (Kadikma, 2018)
This study aims to describe the visual thinking process of mental retardation students in understanding quadrilateral by using origami as the media. Visual thinking in this study is based on the visual-steps of thinking according to Balton (2011). Visual thinking can be used to help students with mental retardation in understanding geometry’s object which has abstract characteristic. Origami media is used as a learning media to improve the visualization ability of students with mental retardation. The type of this research is descriptive research with qualitative approach to give more emphasis on the visual thinking of the mental retardation students than the result of his work. This research was conducted on two mental retardation students of grade nine in SLB Negeri Jember. The instruments of this study are interview guidelines, questions, origami media and validation sheets. The results showed that mental retardation students with assisted origami media could understand rectangles and rectangles based on their properties, determine angles, determine diagonals on rectangles and define diagonal definitions. Keywords: visual thinking, metal retardation students, origami media